Why healthy sleep is good for business. (October 2019) - Barnes, Christopher M.; Watson, Nathaniel F.
Summary: People spend large portions of their lives working, often to the detriment of sleep. Businesses often ignore the importance of employee sleep despite evidence showing sleep health is crucial to positive employee outcomes. In this review we address the effect of sleep on employee health, performance, and workplace relationships. We examine the impact of work characteristics on employee sleep. Finally, we discuss opportunities for businesses to improve employee sleep to maximize success.